(untitled) (University Journal of Zoology, Rajshahi University, 2010)
The physical conditions of Beel Koshba consisting of water temperature (25.36±5.12°C/day), water depth (204.96±110.36cm/month) and water transparency (30.91±6.78 cm/day) were recorded. The chemical parameters of total hardness, alkalinity, pH, DO, CO2 and ammonia were 146.60±13.36 mg/l, 143.30±9.33 mg/l, 7.05±0.75, 6.03±1.08 mg/l, 8.64±0.88 mg/l and 0.73±0.31 mg/l respectively. A total of 54 species of different vegetations 123 species of phytoplankton and 73 species of zooplankton were recorded from the beel. A total of 104 species of fish and Annelids (8), arthropods (12), molluscs (15), amphibian (8), reptiles (21), avis (40) and mammals (12) were identified. Pesticidal toxic effluents contexts were also observed in the beel ecosystem. Key words: Fisheries; Eco-Biology; Beel Koshba DOI: 10.3329/ujzru.v28i0.5283 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 33-39